A new insight into diagnosis and management of hen egg allergy - Gromek, Weronika; Śliwa, Rafał; Choina, Magdalena; Pukaliak, Roman; Markut-Miotła, Ewa (Journal of Education, Health and Sport, 2022)
Introduction: A chicken egg is a popular dietary component all over the world. An allergy to this nourishment is more often related to egg white than to yolk, and its first symptoms often appear even before the first year of life. Aim of the study: The aim of the study is to present the benefits of molecular diagnostics of allergy in chicken egg allergy. Description of the state of knowledge: To diagnose an allergy to egg proteins, skin prick tests or the determination of antigen-specific immunoglobulins E are used. However, the most verifying test of a reaction to food is a double-blind challenge. The most allergenic proteins in a chicken egg are ovomucoid (Gal d 1), ovalbumin (Gal d 2), ovotransferrin (Gal d 3), A-livetin (Gal d 5) and lysozyme (Gal d 4). Among the aforementioned proteins, ovomucoid and ovalbumin are the main allergens and the most common causes of egg allergy. It is worth noting that thermal treatment reduces the allergenic potential of ovalbumin, as opposed to ovomucoid. This means that in patients allergic to ovalbumin, a raw egg may cause an allergic reaction, while an egg, e.g. baked egg, should not cause symptoms of hypersensitivity. Summary:​​ Based on molecular diagnostics, it is possible to identify allergenic molecules of a chicken egg, such as ovomucoid, ovalbumin or ovotransferrin. This allows for better control of symptoms of hypersensitivity in patients with egg allergy. Egg yolk is a good source of amino acids and fats. Therefore, thanks to molecular diagnostics of allergy, it is possible to verify the validity of an elimination diet or to create a diet based on heat-treated eggs.